2022
DOI: 10.1515/joc-2022-0111
|View full text |Cite
|
Sign up to set email alerts
|

400 Gb/s free space optical communication (FSOC) system using OAM multiplexing and PDM-QPSK with DSP

Abstract: In this work, an optical angular momentum (OAM) multiplexing enabled 400 Gbps free space optical communication (FSOC) system has been proposed using polarization division multiplexed (PDM) quadrature phase shift keying (QPSK) and digital signal processer (DSP) in the receiver. Different weather conditions such as clear weather, rain and fog are explored in proposed system and their deteriorating effects are observed in terms of log BER. Laguerre Gaussian (LG) beams (LG0,0, LG0,13, LG0,40, and LG0,80) are emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 2022, an OTC system at 40 Gbps is reported using NRZ, RZ, and alternate mark inversion (AMI) modulation employing LG00, LG130, LG400, and LG800 OAM beams [ 50 ]. The results revealed that NRZ performed best in terms of BER, and the further research conducted in [ 51 ], NRZ was replaced with PDM-QPSK, and it was seen that the data rate supportability increased 10 times, i.e., 400 Gbps. In OWC systems, OAM beams are not investigated widely and are either limited to theoretical proposals [ 52 ] or restricted to lower earth orbit (LEO) based communications [ 53 ].…”
Section: Introductionmentioning
confidence: 95%
“…In 2022, an OTC system at 40 Gbps is reported using NRZ, RZ, and alternate mark inversion (AMI) modulation employing LG00, LG130, LG400, and LG800 OAM beams [ 50 ]. The results revealed that NRZ performed best in terms of BER, and the further research conducted in [ 51 ], NRZ was replaced with PDM-QPSK, and it was seen that the data rate supportability increased 10 times, i.e., 400 Gbps. In OWC systems, OAM beams are not investigated widely and are either limited to theoretical proposals [ 52 ] or restricted to lower earth orbit (LEO) based communications [ 53 ].…”
Section: Introductionmentioning
confidence: 95%
“…However, due to noisy environments, system performance decreases, leading to overall system failure 19 . With a single FSO connection, the system's performance is enhanced since more channels can be used within a given amount of space because each carrier has its own wavelength or channel 20 . However, these models cannot improve connection capacity, system capability, and user consistency due to unforeseen atmospheric attenuation.…”
Section: Introductionmentioning
confidence: 99%